Hepatic ultrasonic changes in workers exposed to perchloroethylene. Issue 10 (October 1995) - Brodkin, C A; Daniell, W; Checkoway, H; Echeverria, D; Johnson, J; Wang, K; Sohaey, R; Green, D; Redlich, C; Gretch, D
Abstract : OBJECTIVE–To determine if subclinical hepatotoxicity is associated with exposure to perchloroethylene at concentrations commonly experienced in the workplace, and whether surveillance with serum hepatic transaminase activity underestimates such effects. METHODS–Hepatic parenchymal echogenicity on ultrasonography and serum hepatic transaminase activity were compared in 29 community based dry cleaning operators exposed to perchloroethylene, and a control group of 29 non-exposed laundry workers. Perchloroethylene exposure was assessed by work history and air monitoring. RESULTS–Mean hepatic transaminase activities were minimally increased in dry cleaners compared with laundry workers. Increased alanine aminotransferase activities, between 1.0 and 1.5 times the normal limits, were found in five of 27 (19%) dry cleaners compared with one of 26 (4%) laundry workers. In contrast, diffuse parenchymal changes in echogenicity, as determined by hepatic ultrasonography, were increased nearly twofold in dry cleaners, occurring in 18 of 27 (67%) dry cleaners compared with 10 of 26 (39%) laundry workers (P < 0.05), and were most strongly associated with increased perchloroethylene exposure in older dry to dry or wet transfer operations (odds ratio 4.2, 95% confidence interval 1.1-15.3). Mean eight hour time weighted average perchloroethylene exposure for dry cleaners was 16 ppm, which is less than the permissible exposure limit of 100 ppm in the United States. CONCLUSIONS–It was concluded that mild to moderate hepatic parenchymal changes occur more frequently in workers exposed to perchloroethylene than in populations not exposed to chemical solvents, and that these effects are underestimated by serum hepatic transaminase activity.